Whence the fuzziness? Morphological effects in interacting sound changes in Southern British English. Issue 1 (5th April 2017) - Strycharczuk, Patrycja; Scobbie, James M.
Abstract : The fronting of the high-back /uː/ and /ʊ/, as currently seen in Southern British English (SBE), is a rare opportunity to study two similar sound changes at different stages of their phonetic development: /uː/-fronting is a more advanced change than /ʊ/-fronting. Since the fronting in both vowels is restricted from applying before a following final /l/ (e.g., in words like fool or pull ), we can exploit the difference in the phonetic advancement of /uː/ and /ʊ/-fronting to illuminate the nature of 'fuzzy contrasts' affecting vowel+/l/ sequences in morphologically complex words. As recent results show that /uː/-fronting is partially limited in fool-ing (but not in monomorphemes like hula ), we ask whether similar morphological constraints affect /ʊ/ followed by /l/ (e.g., bully vs. pull-ing ). Simultaneously, we consider the question of what phonological generalization best captures the interaction between vowel fronting, /l/-darkening, and morphological structure. We present ultrasound data from 20 speakers of SBE representing two age groups. The data show that morphologically conditioned contrasts are consistent for /uː/+/l/, but variable and limited in size for /ʊ/+/l/. We relate these findings to the debate on morphology-phonetics interactions and the emergence of phonological abstraction.